2007
DOI: 10.1084/jem.20070360
|View full text |Cite
|
Sign up to set email alerts
|

Induction of high-affinity IgE receptor on lung dendritic cells during viral infection leads to mucous cell metaplasia

Abstract: Respiratory viral infections are associated with an increased risk of asthma, but how acute Th1 antiviral immune responses lead to chronic inflammatory Th2 disease remains undefined. We define a novel pathway that links transient viral infection to chronic lung disease with dendritic cell (DC) expression of the high-affinity IgE receptor (FcεRIα). In a mouse model of virus-induced chronic lung disease, in which Sendai virus triggered a switch to persistent mucous cell metaplasia and airway hyperreactivity afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
134
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 182 publications
(137 citation statements)
references
References 45 publications
3
134
0
Order By: Relevance
“…Although type 1 interferons are massively produced by pDC during in vivo and in vitro influenza infection, many other cells, including epithelial cells and alveolar macrophages can produce this cytokine in vivo when pDC were depleted using antibodies [2]. pDC were shown to migrate to MLN following lung infection [2,9,53] but their role in viral antigen presentation seems negligible in vivo, as depletion of pDC prior to influenza infection did not modify clearance of the virus or induction of antiviral CD8 1 T lymphocytes. Another possibility that requires further exploration is the precise contribution of pDC to antiviral antibody production [2].…”
Section: Lung DC Subsets and Antiviral Immunity: Influenza As The Parmentioning
confidence: 99%
“…Although type 1 interferons are massively produced by pDC during in vivo and in vitro influenza infection, many other cells, including epithelial cells and alveolar macrophages can produce this cytokine in vivo when pDC were depleted using antibodies [2]. pDC were shown to migrate to MLN following lung infection [2,9,53] but their role in viral antigen presentation seems negligible in vivo, as depletion of pDC prior to influenza infection did not modify clearance of the virus or induction of antiviral CD8 1 T lymphocytes. Another possibility that requires further exploration is the precise contribution of pDC to antiviral antibody production [2].…”
Section: Lung DC Subsets and Antiviral Immunity: Influenza As The Parmentioning
confidence: 99%
“…In contrast to this concept, some animal models of early life infection suggest that virus infection could lead to allergic sensitization (4,5). In clinical studies, Sigurs and colleagues reported that respiratory syncytial virus (RSV) bronchiolitis leading to hospitalization during infancy was a risk factor not only for asthma but also for allergic sensitization at 13 years of age (6).…”
mentioning
confidence: 99%
“…The acute disease is dependent upon Th2 cells; however, the chronic form depends upon iNKT cells producing IL-13 and driving alternatively activated macrophage development. The alternatively activated macrophages produce IL-13, which maintains the disease and may drive even higher levels of mucous cell metaplasia (6,7). The mechanism connecting the acute to chronic disease is not known.…”
mentioning
confidence: 99%
“…At the same time, IgE is produced against SeV, and subsequent cross-linking of IgE on the conventional dendritic cells leads to release of the chemokine CCL28, which then recruits Th2 cells to the airway. These Th2 cells produce IL-13 and drive the development of airway hyper-reactivity and mucous cell metaplasia, two hallmarks of asthma pathology (6). The SeV-induced disease includes both an acute form (develops by day 21 post-inoculation (PI) SeV) and a chronic form (develops by day 49 PI SeV) (7).…”
mentioning
confidence: 99%